Cellular therapies in rheumatic and musculoskeletal diseases - Pedro Franco-Fuquen; Juana Figueroa-Aguirre; David A. Martínez; Eider F. Moreno-Cortes; Juan E. Garcia-Robledo; Fabio Vargas-Cely; Daniela A. Castro-Martínez; Mustafa Almaini; Januario E. Castro (Journal of Translational Autoimmunity)
A substantial proportion of patients diagnosed with rheumatologic and musculoskeletal diseases (RMDs) exhibit resistance to conventional therapies or experience recurrent symptoms. These diseases, which include autoimmune disorders such as multiple sclerosis, rheumatoid arthritis, and systemic lupus erythematosus, are marked by the presence of autoreactive B cells that play a critical role in their pathogenesis. The persistence of these autoreactive B cells within lymphatic organs and inflamed tissues impairs the effectiveness of B-cell-depleting monoclonal antibodies like rituximab.A promising therapeutic approach involves using T cells genetically engineered to express chimeric antigen receptors (CARs) that target specific antigens. This strategy has demonstrated efficacy in treating B-cell malignancies by achieving long-term depletion of malignant and normal B cells. Preliminary data from patients with RMDs, particularly those with lupus erythematosus and dermatomyositis, suggest that CAR T-cells targeting CD19 can induce rapid and sustained depletion of circulating B cells, leading to complete clinical and serological responses in cases that were previously unresponsive to conventional therapies.This review will provide an overview of the current state of preclinical and clinical studies on the use of CAR T-cells and other cellular therapies for RMDs. Additionally, it will explore potential future applications of these innovative treatment modalities for managing patients with refractory and recurrent manifestations of these diseases.